Characterising populations of Puccinia striiformis f. sp. tritici (Pst) using molecular markers - Alvi, Adeelah (2017)
As the world population is projected to increase from 6 to 9 billion by 2050, the demand for global food production is rising (United Nations, 2013). Protecting domesticated crops has become a challenge due to the emergence of pathogenic diseases, which are restricting environmentally sustainable food production. The plant pathogen Puccinia striiformis f. sp. tritici (Pst) most commonly known as yellow rust, is one of the devastating diseases of wheat (Triticum spp.), a major food source globally (Cantu et al., 2011). Rust fungi are an important group of pathogens that pose major concerns for agriculture globally as wheat is a host to three rust diseases, yellow, brown and stem rust. Puccinia striiformis f. sp. tritici (Pst) is a fungus producing dikaryotic urediniospores that spread sporadically causing global epidemics of wheat yellow rust. Serious implications of this rust pathogen have been reported as it continues to spread in various wheat growing regions of the world including China (Duan et al., 2011), Pakistan (Bux et al., 2011), Australia (Welling, 2007), the USA (Milus et al., 2006), and the UK (Cantu et al., 2013). Losses are particularly high in cases when the epidemic is associated with an exotic strain that has not been considered in breeding for resistance locally (Walter et al., 2016). Recently, the evolution of yellow rust pathotypes has been documented by Hovmoller et al. (2016); this study details the migration of rust pathotypes worldwide. They illustrated the emergence of new exotic races displaying a significantly higher genetic diversity than a previous clonal population. The Himalayan and near-Himalayan regions have been documented as the centre of diversity, as this is the place where most sexual reproduction appears to occur (Ali et al., 2010; Ali et al., 2014), whilst in other parts of the world the evidence is that there are clonal introductions that then evolve by stepwise mutation (Wellings et al., 2007; Ali et al., 2014, Hubbard et al., 2015; Hovmoller et al., 2015). This study confirmed these findings with data from Illumina sequencing in chapter 3 and AFLP results from chapter 2 that display an overall distinction between new and old isolates. Developing a better understanding of pathogenicity and virulence factors is essential to reduce the severity of this obligate biotrophic fungus. The aim of this research project was to identify molecular markers linked to specific pathotypes of yellow rust through a random molecular marker approach such as Amplified Fragment Length Polymorphisms (AFLP), and also identify molecular markers such as Single Nucleotide Polymorphisms (SNPs) in potential effector genes, using a targeted NGS approach (Illumina Miseq). Both approaches enabled the comparison of genomes of old and new pathotypes of Pst, and enabled us to explore the association of both types of markers with virulence/avirulence phenotypes of isolates, with the aim of developing markers that could be used to test collections of spore samples using rapid molecular techniques to identify their pathotypes. Using a targeted approach and sequencing potential effector protein regions, identifying presence/absence of genes correlated with presence/absence of avirulence genes using data obtained from chapter 3 proved to be a successful method. This thesis found that many of the genes correlated with the older virulences, and only one gene (Pst130_4892) shared any correlation with a new virulence (AvrSte). In summary, it can be concluded that genes Pst43_3149, Pst877_18061, Pst0821_12746, Pst877_3038, Pst43_20465, Pst43_2877, Pst21_14230, Pst21_18506, Pst877_4028, Pst130_4892 from the 147 studied potential effector proteins, could be known avirulence genes, since polymorphisms and/or presence/absence of them showed correlation with particular Avrs. Anlaysing AFLP data made it possible to correlate specific AFLP markers to virulence/avirulence traits. The sufficiency of markers to distinguish between the two distinct populations was reflected through the correlation with virulences. Virulence for the resistant genes Yr1, Yr2, Yr3, Yr4, Yr9, and Yr17 was identified in most isolates suggesting these virulences are now fixed in the population. Overall, this thesis has identified some markers potentially linked to specific virulence phenotypes. Future studies, using more isolates and gene expression studies should focus on confirming which markers to develop further so that a toolkit of primers can be developed for rapid identification of pathotypes in the field.